Marine algae for feeding Geo-duck larvae at Vandon, quang ninh province - Nguyễn Thị Hoài, Hà (2015)
Quang Ninh is a north-east province with about 250 km coast line, and approximately 2000 islands in a wide range of sizes. This provides a large water surface area, tidal flats and promontories, where many valuable and rare marine species habit. One of them is Geo-duck (Tuhai). Geo-duck is a bivalve species, commonly in Halong Bay. At present, the species is a special food with high nutrient. Fisher exploitation is usually from nutural resource. As the result, Geo-duck clam resource is decreasing seriously. Therefore, researches on biological characteristics of Geo-duck for sustainable development and conservation of this resource is demanded. For people of North Vietnam, Geo-duck culture is almost a new job. They usually collect large individuals while small ones will be rejected into seabed. In order to help fishers and businessmen obtain fundamental knowledge of artificial production of seeds along with culture, we establish a process of Nanochloropsis, Isochrysis, Chraetoceros, Chlorella, marine algae culture. Biomass are gathered by simple method. Fresh, high value nutrient food resoure is provided on the spot. These conditions will facilitate Geo-duck cultivation which is in the process at Van Don district, Halong Bay, Quang Ninh province, Vietnam.